A model for uranium mobility in groundwater in the Grand Pré region, Nova Scotia, Canada - Samolczyk, Mary; Spooner, Ian; Stanley, Clifford (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2012)
ABSTRACT Elevated levels of uranium that surpass maximum allowable concentrations have been recognized in some well water samples throughout Nova Scotia. In this study we examine the influence of redox conditions and regional geology on the mobility of uranium in groundwater in the Grand Pré region, located in the eastern end of the Annapolis-Cornwallis Valley in southwestern Nova Scotia. The study site is underlain by carbon-rich shale and arkosic sandstone of the Late Mississippian Horton Bluﬀ Formation and the arenaceous sandstone of the Triassic Wolfville Formation. Water samples from drilled wells were analyzed on site for various water quality parameters (pH, conductivity, temperature, dissolved oxygen) and in the laboratory to determine alkalinity and cation (72) and major anion (9) concentrations. Several samples exceeded Health Canada (2011) limits for uranium (20 μg/L) with values up to 50.8 μg/L and aesthetic objectives (AO) for iron (up to 605 μg/L), manganese (up to 2.28 mg/L) and other cations. Data show that diﬀerent redox conditions occur in the study area. The geospatial arrangement of the chemical data suggests that the lithology of the underlying aquifer strongly influences the availability of uranium in groundwater. Reduced groundwater in Horton Bluﬀ sandstone typically contains elevated concentrations of Fe 2+ and Mn 2+ , whereas groundwater containing high concentrations of U is found primary in oxidizing environments in quartz arenite sandstone units in the Wolfville Formation. Consumption of groundwater in the Grand Pré region may pose a health risk; however, the level of risk remains unknown. This study emphasizes that in the area of Grand Pré, water that is considered aesthetically undesirable (containing high Fe and Mn) may pose less of a health risk (low U) than waters that are aesthetically pleasing.